FACTOR ANALYSIS OF ADMINISTRATIVE BARRIERS TO ENTREPRENEURIAL ACTIVITIES - Igorevna Bushueva, Ludmila; Fodorovna Popova, Yulia; Pirvelievich Shikverdiev, Arif (Revista Inclusiones, 2020)
This paper presents the results of a multivariate factor analysis of administrative barriers to entrepreneurial activities in the regional market. As the initial information, the authors used the data of an informational and analytical report on the status and development of the competitive environment in the markets of goods and services of the Komi Republic (Russia) in 2018 prepared by the authors of the paper for the Ministry of Economy of the Komi Republic based on monitoring administrative barriers and assessing the competitive environment by business entities. As a result of the analysis, the authors have identified four enlarged groups of factors that impede the development of entrepreneurial activities in the republic, which are associated with legislative barriers, restrictions on access to government orders/public procurements, restrictive factors of interaction with representatives of government agencies and unequal business conditions. It is proposed to use the analysis results to develop measures for promoting the development of the entrepreneurship environment in the Komi Republic.